Gas chromatography in air pollution analysis - Berezkin, V. G. (Viktor Grigorevich), 1931- (Journal of chromatography library ;, 1991)
Air pollution determination is one of the most important fields of gas chromatography application in practice. This book provides a systematic description of the main stages of air pollution determination, ranging from sampling problems to the quantitative estimation of the acquired data. Special attention is paid to the problem of gas, vapor, spray and solid particles extraction from air. The main methods of sampling procedure, namely, container utilization, cryogenic concentration, absorption, adsorption, chemisorption and filter usage, and successive impurities extraction are also handled. Sorption theory and the problems of sorption and desorption efficiency for hazardous impurities being extracted from traps with sorbents are discussed in detail. The practical utilization of different sorbents (silica, activated carbon, polymers etc.) to carry out sampling procedures for 200 main pollutants with known TLV (USSR and USA) is also considered. This highly informative book, reflecting several insufficiently known techniques as well as the experience of both western and Soviet researchers, should be of interest to both beginners and skilled researchers.